Does The Legacy of Colonialism Define Islamism? Analyzing Hallaq’s Critique of Islamic Political Modernity - Ahmad, Danyal; Manzoor Ahmed Kalwar; Khan, Hafiza Sana Rehman; Kalwar, Bashir Ahmed (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
This paper critically examines Wael Hallaq’s argument that contemporary Islamist movements are structurally shaped by colonial modernity and that the modern Islamic state is a hybrid formation rooted in Western political epistemologies rather than an extension of classical Islamic governance. While compelling, these framing risks underemphasize the heterogeneity, agency, and adaptive capacities of Muslim reformist actors. Using Fairclough’s Critical Discourse Analysis and a decolonial framework, the study interrogates the ideological and epistemic assumptions underlying Hallaq’s “impossibility thesis.” The textual analysis shows that his lexical, modal, and metaphorical choices construct a narrative of structural closure that minimizes reformist creativity, while the discursive-practice analysis reveals how his arguments circulate within Western academic paradigms that can unintentionally reinforce epistemic hierarchies. The socio-ideological analysis demonstrates that, although Hallaq exposes the colonial genealogy of the modern state, his emphasis on rupture sometimes obscures how Islamist movements creatively reinterpret shūrā (consultation), maṣlaḥah (public interest), and khilāfah (caliphate), within contemporary political contexts. The findings argue for a more nuanced account of Islamic political agency and situate Islamism within broader debates on decolonial praxis, epistemic plurality, and emerging frameworks such as Islamic multiple modernities, ethical-political subjectivity, and multi-scalar engagements with state power.